An Interphase Microfluidic Culture System for the Study of Ex Vivo Intestinal Tissue - Baydoun, Martha (Micromachines (Basel), 2020)
Ex vivo explant culture models offer unique properties to study complex mechanisms underlying tissue growth, renewal, and disease. A major weakness is the short viability depending on the biopsy origin and preparation protocol. We describe an interphase microfluidic culture system to cultivate full thickness murine colon explants which keeps morphological structures of the tissue up to 192 h. The system was composed of a central well on top of a porous membrane supported by a microchannel structure. The microfluidic perfusion allowed bathing the serosal side while preventing immersion of the villi. After eight days, up to 33% of the samples displayed no histological abnormalities. Numerical simulation of the transport of oxygen and glucose provided technical solutions to improve the functionality of the microdevice.